2020
DOI: 10.1007/s00159-020-00125-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear star clusters

Abstract: We review the current knowledge about nuclear star clusters (NSCs), the spectacularly dense and massive assemblies of stars found at the centers of most galaxies. Recent observational and theoretical works suggest that many NSC properties, including their masses, densities, and stellar populations, vary with the properties of their host galaxies. Understanding the formation, growth, and ultimate fate of NSCs, therefore, is crucial for a complete picture of galaxy evolution. Throughout the review, we attempt to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
290
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(328 citation statements)
references
References 422 publications
36
290
2
Order By: Relevance
“…Such star formation might also be related to the formation of the nuclear stellar cluster (NSC; see e.g. Genzel, Eisenhauer & Gillessen 2010;Schödel et al 2014;Gallego-Cano et al 2020) by providing in situ newly born stars and, since such stars are rotating, it might contribute to its observed rotation (Feldmeier et al 2014;Chatzopoulos et al 2015;Feldmeier-Krause et al 2015;Tsatsi et al 2017;Neumayer, Seth & Boeker 2020). Fig.…”
Section: Spatial Distribution Of Star Formationmentioning
confidence: 99%
“…Such star formation might also be related to the formation of the nuclear stellar cluster (NSC; see e.g. Genzel, Eisenhauer & Gillessen 2010;Schödel et al 2014;Gallego-Cano et al 2020) by providing in situ newly born stars and, since such stars are rotating, it might contribute to its observed rotation (Feldmeier et al 2014;Chatzopoulos et al 2015;Feldmeier-Krause et al 2015;Tsatsi et al 2017;Neumayer, Seth & Boeker 2020). Fig.…”
Section: Spatial Distribution Of Star Formationmentioning
confidence: 99%
“…The Sequoia, G-E/S, Sagittarius Dwarf and the H99 streams have estimated stellar masses (at the time of accretion) of ∼ 1-3×10 8 M ⊙ (e.g., Kruijssen et al 2020). Neumayer et al (2020) have compiled a list of NSCs in the local Universe, along with the properties of their host galaxies. They found that at these host galaxy stellar masses, 75 − 80 per cent of galaxies host NSCs (though this may be a lower limit given the observational challenges in identifying NSCs).…”
Section: Accreted Nuclear Star Clusters and Their Progenitor Galaxiesmentioning
confidence: 99%
“…Nuclear star clusters (NSCs) are some of the densest and most massive clusters known, and occupy the central parts (i.e., nuclear region) of many galaxies. For galaxies with stellar masses above 10 8 M ⊙ , the majority have readily identifiable nuclear clusters (for a recent review, see Neumayer et al 2020) and for galaxies with masses as low as 10 6 M ⊙ the occupation fraction of NSCs remains above 10 per cent. NSCs are unique amongst star clusters as they are the only type (including open clusters, globular clusters, and young massive clusters) that hosts clear evidence for multiple generations of star formation within them or extended star-formation histories (SFHs; see the recent review by Bastian & Lardo 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It hosts a supermassive black hole, Sgr A*, in its dynamical centre that is embedded in a nuclear star cluster (e.g. Schödel et al 2014;Neumayer et al 2020).…”
Section: Introductionmentioning
confidence: 99%